Position statement of the Brazilian Palliative Care Academy on withdrawing and withholding life-sustaining interventions in the context of palliative care - Vidal, Edison Iglesias de Oliveira [UNESP]; Ribeiro, Sabrina Correa da Costa; Kovacs, Maria Júlia; da Silva, Luciano Máximo; Sacardo, Daniele Pompei; Iglesias, Simone Brasil de Oliveira; da Silva, Josimário João; Neves, Cinara Carneiro; Ribeiro, Diego Lima; Lopes, Fernanda Gomes (Associação de Medicina Intensiva Brasileira, 2024)
The issue of withrawing and withholding life-sustaining interventions is an important source of controversy among healthcare professionals caring for patients with serious illnesses. Misguided decisions, both in terms of the introduction/maintenance and the withdrawal/withholding of these measures, represent a source of avoidable suffering for patients, their loved ones, and healthcare professionals. This document represents the position statement of the Bioethics Committee of the Brazilian Palliative Care Academy on this issue and establishes seven principles to guide, from a bioethical perspective, the approach to situations related to this topic in the context of palliative care in Brazil. The position statement establishes the equivalence between the withdrawal and withholding of life-sustaining interventions and the inadequacy related to initiating or maintaining such measures in contexts where they are in disagreement with the values and care goals defined together with patients and their families. Additionally, the position statement distinguishes strictly futile treatments from potentially inappropriate treatments and elucidates their critical implications for the appropriateness of the medical decision-making process in this context. Finally, we address the issue of conscientious objection and its limits, determine that the ethical commitment to the relief of suffering should not be influenced by the decision to employ or not employ life-sustaining interventions and warn against the use of language that causes patients/families to believe that only one of the available options related to the use or nonuse of these interventions will enable the relief of suffering.
Keywords: Bioethics; Clinical decision-making; Consensus; Ethics, medical; Palliative care; Withholding treatment